Anti‐Müllerian hormone exhibits a great variation in infertile women with different ovarian reserve patterns. (17th April 2017) - Gorkem, Umit; Kucukler, Ferit Kerim; Togrul, Cihan; Gungor, Tayfun
Abstract : Background: Several conflicting studies with results on the biological variability of serum anti‐Müllerian hormone (AMH) levels have been reported. Most of the studies have not focused on whether the level of AMH fluctuations shows variability by a baseline ovarian follicular reserve. Aim: To reveal whether intracyclic variation in AMH levels occurs among women with adequate, high and diminished ovarian reserve patterns. Study design: In this prospective cross‐sectional study, 171 infertile women between the ages of 18 and 42 years were recruited. All participants were divided into three types of ovarian reserve patterns (adequate, high and diminished). Serum samples were tested for levels of follicular AMH (F‐AMH), luteal AMH (L‐AMH), estradiol (E2), and follicle stimulating hormone (FSH) and progesterone. Results: The median age of the 171 participating women was 28 (18–42) years. The three ovarian reserve groups had similar body mass index (BMI) and E2 ( P  = 0.797 and P  = 0.135, respectively). The serum AMH levels of all women and the three ovarian reserve groups in the follicular phase were higher compared to those in the luteal phase ( P  <   0.001). There were strong positive correlations between follicular and luteal AMH levels in adequate, high and diminished reserve groups (Spearman r  = 0.864, P  < 0.001 vs r  = 0.899, P  < 0.001 vs r  = 0.863, P  < 0.001, respectively). Conclusion: Serum AMH levels were higher during the follicular phase than the luteal phase in women with adequate, high and diminished ovarian patterns. Since the highest AMH levels are demonstrated during the follicular phase, the optimal time to measure AMH concentration might be during the follicular phase.